The role of the non-indigenous pumpkinseed Lepomis gibbosus (Actinopterygii: Centrarchidae) in the life cycle of Bothriocephalus claviceps (Cestoda: Bothriocephalidae) in Europe - Kvach, Yuriy; Tkachenko, Maria Yu; Bartáková, Veronika; Zięba, Grzegorz; Ondračková, Markéta (Parasitology research, 2021)
Infection of non-indigenous pumpkinseed (Lepomis gibbosus, Centrarchidae) with the bothriocephalidean cestode Bothriocephalus claviceps (Cestoda: Bothriocephalidae) was confirmed at several sites in the lower Oder river basin in Poland. The preferred host for this cestode species is the European eel (Anguilla anguilla), with a wide range of other fish species serving as paratenic hosts. The pumpkinseed showed a relatively high prevalence and abundance of larvae, along with several mature and gravid specimens, thereby confirming development of B. claviceps to the adult stage in an alternative host. As such, the pumpkinseed may represent an additional definitive host for this cestode, in addition to its role as a paratenic host, as previously recorded in other European regions. Our results indicate that inclusion of pumpkinseed as an additional definitive host in the cestode's life cycle, high infection of pumpkinseed with B. claviceps larvae and inclusion of pumpkinseed in the eel's diet could potentially lead to increased parasite pressure on native fish hosts. Further comparative studies or experimental testing will be required to confirm this.
Keywords: Anguilla; Host-parasite interaction; Fish Diseases; Evropa; Cestoda; zvířata; zavlečené druhy; Europe; Perciformes; Introduced Species; Aquatic invasions; stadia vývoje; nemoci ryb; Animals; Life Cycle Stages; Cestode; Pumpkinseed; Oder river basin